Affective Interaction with a Virtual Character Through an fNIRS Brain-Computer Interface - Aranyi, Gabor; Pecune, Florian; Charles, Fred; Pelachaud, Catherine; Cavazza, Marc (Frontiers in Computational Neuroscience, 2016)
Affective Brain-Computer Interfaces (BCI) harness Neuroscience knowledge to develop affective interaction from first principles. In this paper, we explore affective engagement with a virtual agent through Neurofeedback (NF). We report an experiment where subjects engage with a virtual agent by expressing positive attitudes towards her under a NF paradigm. We use for affective input the asymmetric activity in the dorsolateral prefrontal cortex (DL-PFC), which has been previously found to be related to the high-level affective-motivational dimension of approach/avoidance. The magnitude of left-asymmetric DL-PFC activity, measured using fNIRS and treated as a proxy for approach, is mapped onto a control mechanism for the virtual agent’s facial expressions, in which Action Units are activated through a neural network. We carried out an experiment with 18 subjects, which demonstrated that subjects are able to successfully engage with the virtual agent by controlling their mental disposition through NF, and that they perceived the agent’s responses as realistic and consistent with their projected mental disposition. This interaction paradigm is particularly relevant in the case of affective BCI as it facilitates the volitional activation of specific areas normally not under conscious control. Overall, our contribution reconciles a model of affect derived from brain metabolic data with an ecologically valid, yet computationally controllable, virtual affective communication environment.